∫x E xDx

∫ x e^x dx= ∫ x d(e^x)= x e^x - ∫ e^x dx,分部积分法= x e^x - e^x + C= (x - 1)e^x + C

∫x(e^x) dx=∫xd(e^x)=xe^x-∫(e^x) dx=xe^x-e^x+C

∫(e^x)/xdx=∫(1+x+x^2/2!+……+x^n/n!+……)/xdx =∫(1/x+1+x/2!+x^2/3!+……+x^(n-1)/n!+……)dx =lnx+x+x^2/(2*2!)+……+x^n/(n*n!)+……

是正无穷吧∫x/e^xdx=-∫xe^-xd(-x)=-∫xde^-x=-xe^(-x)+∫e^-xdx=-xe^(-x)-e^(-x) (1→+∞)=-(x+1)/e^x (1→+∞)x+∞lim-(x+1)/e^x=lim-1/e^x (洛必达法则)=0所以原式=0+2/e=2/e

∫xedx=-∫xd(e)=-xe+∫edx=-xe-e +C=-(x+1)e+C

∫2^x*e^xdx=∫(2e)^xdx=(2e)^x /ln(2e)+c=2^x*e^x /(1+ln2)+c

原式=-1/2 ∫e^(-x)d(-x) 令t=-x则积分 =-1/2 ∫e^tdt = =-1/2e^t = -1/2e^(-x)

用分部积分:∫xe^x dx=∫xd(e^x)=xe^x-∫e^xdx=xe^x-e^x+C=(x-1)e^x+C

∫xe^xdx =xe^x-∫e^xdx= xe^x-e^x+c

∫x*e^(-x)dx =-∫x*e^(-x)d(-x) =-∫xd[e^(-x)] =-xde^(-x)+∫e^(-x)dx =-xde^(-x)-∫e^(-x)d(-x) =-xde^(-x)-e^(-x)+C =-e^(-x)*[x+1]+C 希望帮助你解决了问题.

相关文档

e的 x方的原函数
求不定积分∫x e xdx
e x如何积分
e x dx 求导
∫e x2dx求导
∫e xcosxdx
x e x定积分
∫xye xdx求导
∫4x e∧ x
∫x 3e x dx
∮x∧2 arctanxdx
x2exdx的不定积分
∫e x 2 不定积分
fe∧ x e∧xdx
x e的 x次方定积分
指数分布的原函数
e xdx如何计算
∞ e ∞等于多少
电脑版